2014
DOI: 10.2134/ats-2013-0017-rs
|View full text |Cite
|
Sign up to set email alerts
|

Mowing Before or After an Herbicide Application Does Not Influence Ground Ivy (Glechoma hederacea ) Control

Abstract: Many turfgrass extension bulletins and herbicide labels recommend prolonging or suspending mowing practices 1 day or more before and/or after herbicide applications to increase efficacy. However, the effect of mowing timing on herbicide efficacy has not been sufficiently explored. Field experiments were conducted to evaluate the influence of herbicide selection and mowing timing relative to herbicide application on the control of ground ivy (Glechoma hederacea L.). The three mowing treatments included mowing 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Other research indicated Imprelis SL was an excellent new herbicide for use in turfgrass (Beck et al, 2014), and our research showed it also had minimal to no volatility. Unfortunately, during the course of our research Imprelis SL was implicated in multiple cases of tree damage, apparently caused by root uptake of the herbicide, and has been removed by the manufacturer from the turfgrass market (V.B.…”
Section: Effects On Tomatoes Exposed To Herbicide Treated Turfgrass Isupporting
confidence: 63%
“…Other research indicated Imprelis SL was an excellent new herbicide for use in turfgrass (Beck et al, 2014), and our research showed it also had minimal to no volatility. Unfortunately, during the course of our research Imprelis SL was implicated in multiple cases of tree damage, apparently caused by root uptake of the herbicide, and has been removed by the manufacturer from the turfgrass market (V.B.…”
Section: Effects On Tomatoes Exposed To Herbicide Treated Turfgrass Isupporting
confidence: 63%
“…Triclopyr provided effective and consistent ground ivy control (78–98% reduction) in Kentucky bluegrass in past research (Beck et al, 2014; Kohler et al, 2004b; Reicher and Weisenberger, 2007). Fluroxypyr was also effective against ground ivy (87% reduction), although it was less effective than triclopyr (98% reduction) (Reicher and Weisenberger, 2007).…”
mentioning
confidence: 66%
“…In Michigan, Hanson and Branham (1988) observed that mid‐to‐late October herbicide applications resulted in greater levels of dandelion control than September applications when evaluated the following spring. Previous reports have also documented the efficacy of fall herbicide applications for ground ivy control (Beck et al, 2014; Kohler et al, 2004b; Reicher and Weisenberger, 2007). Fall herbicide applications from 1 September to 1 November provided greater ground ivy control than applications made after 15 November in West Lafayette, IN (Reicher and Weisenberger, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carfentrazone-ethyl (shoot-absorbed) plus 2,4-D (root-absorbed) plus dicamba (root-and shoot-absorbed) plus mecoprop (mostly root-absorbed) (Speedzone 2.2L; PBI Gordon, KS City, MO) is effective for the control of many broadleaf weeds and goosegrass-the only grassy weed listed on the label (http://www.cdms. net/ldat/ld61R001.pdf) (Beck et al, 2014). The site of herbicide uptake is an important factor to consider when developing techniques to reduce turfgrass injury.…”
mentioning
confidence: 99%